2020
DOI: 10.3390/healthcare8030243
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Privacy and Data Security across Healthcare Applications Using Blockchain and Distributed Ledger Concepts

Abstract: Nowadays, blockchain is developing as a secure and trustworthy platform for secure information sharing in areas of application like banking, supply chain management, food industry, energy, the Internet, and medical services. Besides, the blockchain can be described in a decentralized manner as an immutable ledger for recording data entries. Furthermore, this new technology has been developed to interrupt a variety of data-driven fields, including the health sector. However, blockchain refers to the distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…However, the classic ABE does not fully ensure data privacy, effective collision prevention, or assurance of attribute revocation-based forward and backward security. Revocation has also resulted in significant computing costs [ 18 , 28 , 29 ], respectively. In order to increase data storage security and cloud computing performance, implementing blockchain technology and its security measures will become a critical study area.…”
Section: Cloud Security Systemsmentioning
confidence: 99%
“…However, the classic ABE does not fully ensure data privacy, effective collision prevention, or assurance of attribute revocation-based forward and backward security. Revocation has also resulted in significant computing costs [ 18 , 28 , 29 ], respectively. In order to increase data storage security and cloud computing performance, implementing blockchain technology and its security measures will become a critical study area.…”
Section: Cloud Security Systemsmentioning
confidence: 99%
“… 49 Such studies identified in this systematic review varied in their approach, with strategies including the use of shared keys in the event of the death of the patient (key-holder); 50 electronic medical records maintenance in a unified viewpoint; 51 secure cloud-based electronic medical records; 52 enhanced interoperability; 53 fine-grained access; 54 and privacy-preservation techniques. 50 , 55 , 56 In one of the few clinically trialled blockchain platforms we found, Lo and colleagues 57 integrated medical data from the National Medical Record system in Taiwan with clinic electronic medical records to create an alliance-based medical referral system. They also used a patient-centric approach by further developing an additional blockchain-based decentralised application to grant access rights and data control to patients, which allowed them to demonstrate a viable decentralised referral system and strong patient interest in accessing their own medical data.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the time series analysis revealed that the cost of data breaches and number of data breaches will increase in near future. Liu et al [29] proposed a system based on blockchain and distributed ledger-based improved biomedical security system (BDL-IBS), in order to strengthen privacy and security in healthcare applications. Chadwick et al [30] designed an architecture for sharing the cyber threat information.…”
Section: Related Workmentioning
confidence: 99%